Development and characterisation of high performance plastics based on liquid crystalline polymer blends and composites - Lee, Mun Wai. (2008)
From this course of work, the concept of an in-situ hybrid nanocomposite has been demonstrated to be a feasible approach to develop new materials to meet the demanding stipulation of numerous applications.